Cloning and sequence analysis of three variants of the gene encoding alkaline xylanase C from the alkaliphilic bacillus sp (NCL 87-6-10) - Sharma, Poonam; Rele, Meenakshi V.; Kumar, Lalitha Sunil (Biochemical Genetics, 2013)
Alkaline xylanase C from the alkaliphilic Bacillus sp. (NCL 87-6-10) has a low molecular weight and alkaline pI and is cellulase-free, properties compatible with its use in the prebleaching of pulp. We report here the cloning and sequence analysis of three variants of the gene encoding xylanase C; xyl C1, xyl C2, and xyl C3. In phylogenetic analysis, the three xylanase C variants clustered into a single group along with other reported alkaline xylanases. Residues contributing to the alkaline pH were present in all three variants. DNA and protein sequence comparison of these variants with other reported alkaline xylanases revealed silent mutations, some of which are due to codon preference in the respective organisms. The recombinant Xyl C1 that was successfully expressed in E. coli BL21 (DE3) had properties similar to the native enzyme.
Keywords: Alkaline xylanase C; Alkaliphilic Bacillus sp (NCL 87-6-10); Cloning; E. coli BL21 (DE3) expression; Sequence analysis